Young men, masculinities and sex education - Limmer, Mark (Sex Education : Sexuality, Society and Learning, 2010)
This paper draws on focus group and interview data from 45 young men from the north of England to explore the barriers to effective sex and relationships education (SRE). Recent policy debates in relation to establishing statutory SRE in schools provide an opportunity to revisit how it is currently delivered to, and received by, young men. The paper considers the central role played by masculinities and how this role is mediated by social exclusion and poor engagement; it is suggested that addressing masculinities directly should be a priority for future SRE. In conclusion, some tentative approaches to addressing the issues are suggested.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; discipline; europe; hommes*; jeunes adultes; masculinité; périodes historiques; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle